Gender comparisons on the cyber-counseling and face-to face counseling approaches - Nor Zainudin, Zaida; Mohamad Yusof, Yusni (Human Resource Management Academic Research Society, 2018)
Cyber-counselling has been widely offered and has become one of the alternative approach in counseling help. However, the effectiveness of this service is highly debated among scholars. Some scholars claimed that the cyber-counseling will give a great help to men, and some other scholars stated that cyber-counseling will benefit the women. There was also a study showing no difference between the gender in choosing and benefiting from cyber-counseling services . With these arguments, this study aims to see the impact of gender on client satisfaction in face-to-face counseling and cyber-counseling approaches. Quasi-experimental study using The Non-Equivalent Post-test Only Design is applied in this study. A total of 60 subjects were involved and conducted in two study groups; control group using Face-to-Counseling approach and experimental group using Cyber-counseling approach. Quantitative data was obtained using the Client's Satisfaction Inventory Short-Form (CSI-SF) questionnaire. The findings show there are differences between the Gender and Client Satisfaction in both approaches and the results of the Two-Way Anova analysis show that there is a major interaction between the Gender and Client Satisfaction. Further analysis using One Way Anova shows the interaction effect that male clients get more satisfaction in the Cyber-counseling approach while female clients get more satisfaction in face-to-face counseling. The empirical data shows that the male benefited in cyber-counseling approach and the possible reasons are discussed.